Dukungan Lingkungan Terhadap Keefektivan Komunikasi Masyarakat Aceh di Bogor dalam Pengelolaan Dampak Tsunami - Yusnidar .; Sumardjo .; R.W.E. Lumintang (Institut Pertanian Bogor, 2008)
To investigate the communication efectiveness of Acehnese community in Bogor on tsunami impact management, ithas been done an explanatory research. The objectives of this research are to analyze: (1) how far thecommunication processes of Acehnese community in Bogor on tsunami impact management correlate with theirindividual environments?, (2) how far the communication efectiveness correlate with their individual environments?,and (3) are individual environment aspects correlate each other? The study was conducted in Bogor district andBogor City from April until June 2006. The samples was determined by disproportional stratified random sampling,according to group and gender of Acehnese community. The respondents were 90 persons consist of 30 persons ineach group (permanent Acehnese community, undergraduate students, and postgraduate students), divided into 15male and 15 female. The result showed that: Firstly, the communication processes of Acehnese community in Bogoron tsunami impact management are influenced by their individual environments. The higher environments supportthe higher communication processes done. Secondly, the environments support (primarily from frends, neighbors,media, social supports) would influence the communication efectiveness of Acehnese community in Bogor, expressedin their good knowledge on tsunami impact management. Thirdly, individual environment aspects correlate eachother. Family support was the most important aspect because it could influence neighbor and social supports as wellas media availability.